A cross-cultural comparison of dual career environments for elite athletes in Switzerland, Denmark, and Poland - Küttel, A.; Krogh Christensen, M.; Zysko, J.; Hansen, J. (International Journal of Sport and Exercise Psychology, 2018)
To achieve top-level performance in elite sports, athletes engage in a long-term, deliberate practice which often conflicts with educational commitment (Stambulova & Ryba, 2013). Consequently, many elite athletes face the dilemma of whether to undertake a dual career (i.e., combining sports with education and/or work) or to focus solely on sports (Stambulova, Engström, Franck, Linnér, & Lindahl, 2015). Athletes who focus exclusively on their athletic career are at risk of athletic identity foreclosure, which can lead to adaptation difficulties when ending the sports career (Grove, Lavallee, & Gordon 1997). Dual career pathways have been shown to be helpful for balancing sports and other spheres of an athlete's life (Wylleman & Lavallee, 2004). Other benefits, such as reduced stress level, better conditions for developing life skills, social benefits, enhanced career/retirement planning, and improved future employment prospects have been associated with a dual career (e.g., Aquilina, 2013). The continuously growing demands in international sports have led to an increasing trend of convergence of national elite sports systems (Houlihan & Green, 2008). According to Digel (2005), talent development programmes, elite sports facilities, financial support for athletes, and flexibility in education are examples of common elements of elite sport systems. Concerning dual career, the elite sports comparative study SPLISS (De Bosscher, Shibli, Westerbeek, & van Bottenburg, 2015) concluded that countries adopt various strategies for integrating academic and sporting careers, but no best approach could be identified as giving a competitive advantage. Aquilina and Henry (2010) investigated social policies that address the educational needs of elite athletes and, consequently, classified the approaches of the EU Member States to promoting higher education (i.e., level 5 and up on the ISCED, 2011) in a four-fold typology: (1) state-centric provision based on legal grounds; (2) state as a facilitator, fostering formal agreements between educational and sporting bodies; (3) national federations/sports institutes as facilitators or mediators between athletes and educational bodies; and (4) a "laissez-faire" approach, which does not have a formal structure in place. These different national approaches seem to have an influence on athletes' educational levels. To illustrate, 39% of the Swiss athletes had obtained a tertiary education degree at retirement, compared to 62% of the Danish and 85% of the Polish athletes (Kuettel, Boyle, & Schmid, 2017).